HRVATSKI CRKVENOSLAVENSKI PRIJEVOD BULE PAPE BONIFACIJA IX. SUPERNIBENIGNITAS CONDITORIS. - MIHALJEVIĆ, Milan (Slovo (05836255), 2024)
The paper analyzes the Church Slavonic translation of a bull issued by Pope Boniface IX in 1389 on the occasion of the Visitation. Today, 15 copies of this translation from the golden age of Croatian Glagolitism (14-16 century) are known. The text is an integral part of the breviary service and is read in the octave of the Visitation. We compared the text of all copies, listed their differences, and determined that they are all variants of the same translation. The differences between them are relatively small, and can in most cases be explained by editorial interventions by the scribe. The Croatian Glagolitic text is also compared with the Latin original, with special attention paid to deviations from the Latin text. In places where a literal translation would be contrary to a Church Slavonic linguistic norm, the translator changed the word order or the type of phrases from that in the Latin original. He also expanded the text by adding information not contained in the Latin original, and sometimes omitted a word, phrase, or larger part of the text if he considered them redundant. Only in a few places did he misunderstand the text and mistranslate it. This translation is interesting because it shows that Croatian Glagolitic writers were up-to-date and included texts in their liturgical books very soon after they were introduced into Latin books. The oldest copy of the translation is from the First Beram Breviary, which dates to the turn of the 15 century. The other copies are from the second half of the 15 century. We found that the scribe of the First Beram Breviary did not translate the text himself, but rather copied it from an older Glagolitic protograph, which means that the text was translated very soon after the bull was issued.